C-reactive protein: the nexus between inflammation and protein misfolding diseases - Abhishek Roy; Abhishek Roy; Johannes Zeller; Johannes Zeller; Tracy L. Nero; Tracy L. Nero; Tracy L. Nero; Johanna Klepetko; Steffen U. Eisenhardt; Michael W. Parker; Michael W. Parker; Michael W. Parker; et al. (Frontiers in Immunology)
C-reactive protein (CRP), an acute-phase protein primarily produced by hepatocytes in response to pro-inflammatory cytokines, is a widely used clinical marker for inflammation and tissue damage. In its native state, CRP exists in a stable pentameric form called pCRP. Upon interaction with activated cell membranes, pCRP undergoes a transitional conformation change into activated pCRP (pCRP*) and subsequently fully dissociates into its monomeric subunits (mCRP). pCRP* and mCRP interact with C1q and thereby activate the classical complement system pathway and both exert pro-inflammatory effects on platelets and endothelial cells. Although classically recognized as a marker of acute inflammation, CRP is increasingly implicated in the pathogenesis of protein-misfolding pathologies, notably neurodegenerative diseases and amyloidosis. This review explores the complex interplay between CRP, encompassing its isoforms pCRP, pCRP*, and mCRP, and misfolded proteins, examining the specific contributions to inflammation and neurodegenerative disease pathogenesis. We analyze the clinical significance of variations in CRP levels in patients with protein-misfolding diseases, discuss underlying mechanisms, and highlight potential implications of these findings for drug discovery and therapeutic targeting of CRP.